Two-four group educational research designs pretest-posttest interaction, switching replication, and treatment effect - Huelar, Ma. Corazon Senier (2006)
This study compared four-group and two-group educational research design in relation to pretest posttest interaction and switching replication treatment and the influence on treatment effect. It used 8 groups to examine the influence of every combination on the treatment effect. The subjects were four sections of 182-second year high school students of Mandaluyong High School. The instrument was a 30-item achievement test on genetics and evolution. Since this study used four-group designs, further studies can compare the treatment effects of two group or three group designs. Biology teachers can use in class the following sequence of achievement testing and instructional treatments: pretest-initial treatment-initial posttest-switching replication- final posttest.